Chronic high‐fat diet decreased detrusor mitochondrial respiration and increased nerve‐mediated contractions. Issue 6 (10th May 2019) - Powers, Shelby A.; Ryan, Terence E.; Pak, Elena S.; Fraser, Matthew O.; McClung, Joseph M.; Hannan, Johanna L.
Abstract: Aims: To assess the impact of chronic high‐fat diet (HFD) on behavioral voiding patterns, detrusor contractility, and smooth muscle mitochondrial function in male mice. Materials and Methods: Male C57BL/6J mice (6 weeks) were fed a control or HFD for 20 weeks. Bladder function was assessed by void spot assays. Bladders were collected and detrusor contractility to carbachol (10 −9 ‐10 −5  M), and electrical field stimulation (EFS, 0.5–32 Hz) in the presence and absence of atropine was measured. Homogenized detrusor samples were placed in oxygraphs to assess the rate of oxygen consumption of the mitochondria within the detrusor in the presence of different substrates. Mitochondrial hydrogen peroxide (H2 O2 ) emission was measured fluorometrically. Detrusor citrate synthase activity was measured via enzyme activity kit and Western blots assessed the electron transport chain (ETC) protein content. Results: HFD significantly increased body weight, adiposity, and blood glucose levels. HFD mice demonstrated increased voiding frequency and increased EFS‐induced detrusor contractility. There were no changes in detrusor relaxation or cholinergic‐medicated contraction. Mitochondrial respiration was decreased with HFD and H2 O 2 emission was increased. The relative amount of mitochondria in the detrusor was similar between groups. However, ETC complexes V and III were increased following HFD. Conclusions: Chronic HFD increased adiposity, lead to more frequent voiding, and enhanced EFS‐mediated detrusor contractions. Mitochondrial respiration was decreased and H2 O 2 emission increased following HFD. Further research is required to determine if alterations in mitochondrial function could play a role in the development of HFD‐induced bladder dysfunction.